2018
DOI: 10.1111/cas.13896
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S‐transferase Pi 1 is a valuable predictor for cancer drug resistance in esophageal squamous cell carcinoma

Abstract: Esophageal squamous cell carcinoma (ESCC) is a lethal malignancy. However, there are few useful markers for diagnosis and treatment. Glutathione S‐transferase Pi 1 (GSTP1) has been reported as a predictor of malignancy or anticancer drug resistance in some cancers. We investigated the association of GSTP1 expression with the malignancy or drug resistance in ESCC cell lines and clinical tissue samples. Proliferation and apoptosis assays regarding GSTP1 expression were examined in ESCC cell lines. Proliferation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…In addition, the effect of GSTP1 on cell proliferation and apoptosis has been examined in esophageal squamous cell carcinoma cell lines. Knocking down GSTP1 in cancer cells significantly decreases cell proliferation, while early apoptosis occurs [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the effect of GSTP1 on cell proliferation and apoptosis has been examined in esophageal squamous cell carcinoma cell lines. Knocking down GSTP1 in cancer cells significantly decreases cell proliferation, while early apoptosis occurs [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that several of the identified proteins have already been reported as binding partners, e.g., vimentin; protein disulfide-isomerases PDIA1, PDIA3, and PDIA6; COP9 signalosome complex subunit 4; and elongation factor 1 alpha-1 [ 16 , 17 , 19 , 40 ]. However, only in rare cases have efforts been made to characterize their relevance for cell sensitivity [ 41 , 42 , 43 , 44 , 45 ]. To produce detailed studies, we selected one protein only identified in ovarian cancer cells, one found only in colorectal cancer cells, and one identified in all four cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…GSTP1 is believed to play a significant role in the inactivation of drugs by conjugating them to glutathione with subsequent transportation out of the cells via, e.g., membrane-bound MRP efflux pumps [ 48 , 58 , 59 ]. The enzyme has been found to be overexpressed in a variety of solid tumors and has also been linked to malignant potential and poor outcomes [ 45 , 60 ]. Under normal conditions, GSTP1 is bound to c-Jun N -terminal kinase (JNK), preventing its phosphorylation and therefore inhibiting downstream signaling [ 30 , 33 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, there was a significant association between GSTP1 expression in resected tissue and biopsy samples in patients with esophageal squamous cell carcinoma without neoadjuvant chemotherapy. GSTP1 was related to malignant potential and may be a predictive marker of drug resistance in esophageal squamous cell carcinoma patients [143]. A previous study found a significant association between the variant GSTP1 Ala114Val genotype and increased risk of recurrence and death.…”
Section: Usefulness Of Gstp1-1 Enzymatic Activity In Some Pathologmentioning
confidence: 99%